„Szépen, igeragozás szerint beszélnek” Mi, ti és ők, avagy hogyan látják nyelvváltozataikat a kárpátaljai magyarok - Csernicskó István; Черничко Степан; Csernicsko Istvan (MTA Nyelvtudományi Intézet-Gramma Nyelvi Iroda-Konstantin Filozófus Egyetem Közép-európai Tanulmányok Kar-Tinta Könyvkiadó, 2009)
Tanulmányunkban az egyén felől közelítjük meg a nyelv közösségteremtő és csoportmeghatározó szerepét, s azt vizsgáljuk, hogyan jelenik meg az anyanyelv és annak változatai a kárpátaljai magyar közösség önmeghatározásában. Fő forrásként a kárpátaljai magyar hanganyagtár1 600 mélyinterjúját használjuk fel, melyeket 2003 és 2008 között készítettünk, Kárpátalja valamennyi magyarok lakta települését érintve.

Abstract. Based on 600 linguistic interviews we analyze Ukrainian (Transcarpathian) Hungarians’ linguistic attitudes towards their own dialect. The aim of the study is to show on the basis of the interviews what kind of role do the Hungarian language and regional dialects play in the national, regional and local identity of the Transcarpathian Hungarian autochthonous national minority. The study proves that the Hungarian language is a key factor of the national identity of the given national and linguistic minority. Regional dialects help to distinguish Hungarians living in Transcarpathia from Hungarians living in Hungary. While local dialects make possible for speakers to express identity to their own settlement, domicile. Analysis also shows that when Transcarpathian Hungarians go to Hungary, they frequently have to hide the main characteristics of their regional dialect. People do that in order to avoid language based stigmatization and/or discrimination.
We, you and they: how Transcarpathian Hungarians see their own language variant
Keywords: igeragozás; Kárpátalja; identitás